Designing 3D Polymeric Structures through Capillary Wetting on Colloidal Monolayer (Adv. Funct. Mater. 1/2023). (3rd January 2023) - Lee, Hyeong Jun; Park, Sanghyuk; Kim, Jong Bin; Kim, Shin‐Hyun
Abstract : Capillary Wetting of Colloidal Monolayers In article number 2208402, Jong Bin Kim and co‐workers study capillary wetting of colloidal monolayers by a limited volume of molten polymer, which enables the production of complex wavy surfaces with controlled waviness. The directional metal deposition on the 3D structures develops both plasmonic and diffraction colors which are otherwise difficult to achieve with conventional pseudo‐3D structures.